2007
DOI: 10.1007/s10722-007-9287-5
|View full text |Cite
|
Sign up to set email alerts
|

Recovery, morphological and molecular characterization of globe artichoke ‘Romanesco’ landraces

Abstract: The 'Romanesco' globe artichoke is of substantial economic importance for Italy, its major world producer. The widespread adoption of single early uniform micropropagated clones has led to erosion of local genetic resources. In an attempt to characterise landrace diversity for future breeding activities and/or germplasm conservation, a set of 19 clones derived from plants cultivated in traditional areas of Latium region were typed using a combination of morphological traits (UPOV descriptors) and DNA markers (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
23
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 32 publications
7
23
0
Order By: Relevance
“…fragments present in only one accession) found by Crinò et al (2008) in 'Romanesco' clones is comparable to that observed by Lanteri et al (2004b) and Sonnante et al (2004Sonnante et al ( , 2007 in collections with all the global artichoke types. The predicted heterozygosity was different (0.37 versus 0.67) from that estimated in wild cardoon using SSR markers , probably because SSR loci are associated with a high number of detectable alleles, whereas AFLP and ISSR loci are dominant.…”
Section: The Romanesco Artichokesupporting
confidence: 74%
See 4 more Smart Citations
“…fragments present in only one accession) found by Crinò et al (2008) in 'Romanesco' clones is comparable to that observed by Lanteri et al (2004b) and Sonnante et al (2004Sonnante et al ( , 2007 in collections with all the global artichoke types. The predicted heterozygosity was different (0.37 versus 0.67) from that estimated in wild cardoon using SSR markers , probably because SSR loci are associated with a high number of detectable alleles, whereas AFLP and ISSR loci are dominant.…”
Section: The Romanesco Artichokesupporting
confidence: 74%
“…Some of the studies aim at (i) characterizing these landraces in terms of genetic and molecular profiles; (ii) investigating the genetic variability existing within and among landraces; (iii) identifying genetic resources for the development of future breeding programs. Landraces were clustered on the basis of morphological and molecular traits (Crinò et al 2008;Ciancolini et al 2012). These clusters agreed with the landraces' original area even if no significant correlation between genetic similarity and morphological trait matrices was revealed by the Mantel test.…”
Section: The Romanesco Artichokementioning
confidence: 59%
See 3 more Smart Citations